A Few Remarks About Challenges in Application of Restorative Justice: A Case Study of Bosnia and Herzegovina - Kazic, Ena; Rialda Ćorović (Review of European and Comparative Law, 2022)
Restorative justice is without any doubt one of the most important steps in the development of criminal law, which at the same time increased the level of humanity in the approach towards perpetrators and victims and managed to achieve the principle goals of criminal law. A few decades have passed since its idea and approach was borrowed from the traditional communities that among themselves applied it for centuries and it was transformed into the new approach of justice offering many benefits to the community where it is established. Formally, it has been more than 20 years since Bosnia and Herzegovina embraced restorative justice within its criminal law. This paper aims to discuss how much de facto it has been applied in this country and to present results of interviews with representatives from legal theory and practice where they refer to restorative justice and its major challenges for application and propose mechanisms for overcoming existing difficulties. In this article, the authors use normative, descriptive scientific methods and statistics and interviews as tools for the collection of data.